Upper airway surgery of obstructive sleep apnea in pycnodysostosis: Case report and literature review. Issue 8 (8th April 2014) - Testani, Elisa; Scarano, Emanuele; Leoni, Chiara; Dittoni, Serena; Losurdo, Anna; Colicchio, Salvatore; Gnoni, Valentina; Vollono, Catello; Zampino, Giuseppe; Paludetti, Gaetano; Marca, Giacomo Della
<x xml:space="preserve">Abstract</x> Pycnodysostosis is an autosomal recessive disorder due to a mutation in the cathepsin K gene, which causes a decrease of the bone turnover; a review of the literature suggests that pycnodysostosis is frequently associated with severe respiratory obstruction, which needs surgical treatment. The aim of this paper is to describe the surgical treatment of a 3½‐year‐old girl affected by Pycnodysostosis complicated by a severe sleep‐related respiratory disorder. The surgical treatment, consisting of adenotonsillectomy and palatoplasty, resulted in a striking amelioration of respiratory parameters and increased posterior airway space, and allowed the patient to avoid tracheotomy while awaiting for maxillo‐mandibular surgery. © 2014 Wiley Periodicals, Inc.